2020
DOI: 10.1038/s41598-020-78662-y
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory analysis of Au–Pd bimetallic nanoparticles synthesized with Citrus limon leaf extract and its efficacy on mosquito larvae and non-target organisms

Abstract: The current study provides novel results on the synthesis of bimetallic nanoparticles (BNPs) of gold and palladium (Au–Pd) with an eco-friendly and non-toxic aqueous leaf extract of plant Citrus limon. The BNPs were characterized and toxicity bioassay was examined on the larvae of the pathogen vectors such as Anopheles stephensi and Aedes aegypti mosquitoes. The predation efficiency test was evaluated on the invertebrate non-target organisms such as natural predatory nymphs of dragonfly and damselfly. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…There are some studies which used nanoparticles of selenium (Cittrarasu et al 2021), zinc oxide (Amuthavalli et al 2021), Au-Pd bimetallic (Minal and Prakash 2020), but for these studies they used higher concentration of nanoparticles to get 100% mortality. As compared to above studies, our present investigation revealed 100% mortality of all the larval instars and pupae at very low concentrations of bio-nanocomposites.…”
Section: Mosquito Larvicidal Activitymentioning
confidence: 99%
“…There are some studies which used nanoparticles of selenium (Cittrarasu et al 2021), zinc oxide (Amuthavalli et al 2021), Au-Pd bimetallic (Minal and Prakash 2020), but for these studies they used higher concentration of nanoparticles to get 100% mortality. As compared to above studies, our present investigation revealed 100% mortality of all the larval instars and pupae at very low concentrations of bio-nanocomposites.…”
Section: Mosquito Larvicidal Activitymentioning
confidence: 99%
“…Similarly, synthesized Cu-Zn, ZnO-TiO and Ag-Ni bimetallic nanoparticles have been used as nano-pesticide/insecticide against cotton Mealybug [254], Spodoptera fruggiperda (an important pest of several crops) [255] and Lymphatic filariasis Vector [256]. In addition, Au-Pd have also shown larvicidal activity against mosquito larvae [257]. Another application of bimetallic nanoparticles in agriculture is food packaging.…”
Section: Agriculturementioning
confidence: 99%
“…It should be noted that modifications to the WHO standardized procedures are common. These variations concern mainly the operating conditions during the assay such as the volume of solutions containing the larvae to be tested (100–250 mL) and their concentration (number of larvae per mL) [ 175 , 224 , 231 , 238 , 239 , 240 ]. In addition, some studies report the use of first and second instar larvae in the test even though late third and young fourth instar larvae are recommended [ 241 , 242 , 243 , 244 ].…”
Section: Green Synthesized Plant-based Metallic Nanoparticles As a Mo...mentioning
confidence: 99%